Systematic Literature Review: The Importance Of Work Motivation To Employee Performance - Moh Fildan Nor; Anis Eliyana; Ahmad Rizki Sridadi (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
Work motivation is one of the crucial keys to improving employee performance. This study aims to describe the factors that affect work motivation and explain the influence of work motivation on employee performance. Through the systematic literature review approach, this study identified 34 articles with the publication year 2018 – 2022 that discussed work motivation. The results showed that the factors that affect work motivation include leadership, work environment, employee training, task characteristics, rewards for performance, career path, and commitment. Seventeen articles describe a significant influence of motivation on employee performance. In comparison, the other three articles show that there is an insignificant influence between work motivation and employee performance.